Natural resource revenues and public investment in resource-rich economies in sub-Saharan Africa - Amin Karimu; George Adu; George Marbuah; Justice Tei Mensah; Franklin Amuakwa-Mensah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The general policy prescription for resource-rich countries is that, for sustainable consumption, a greater percentage of the windfall from resource rents should be channelled into accumulating foreign assets such as a sovereign public fund as done in Norway and other developed but resource-rich countries. This might not be a correct policy prescription for resource-rich sub-Saharan African (SSA) countries, where public capital is very low to support the needed economic growth. In such countries, rents from resources serve as opportunity to scale-up the needed public capital. Using panel data for the period 1990-2013, we find in line with the scaling-up hypothesis that resource rents significantly increase public investment in SSA and that this tends to depend on the quality of political institutions. We also find evidence of a positive effect of public investment on economic growth, which also depends on the level of resource rents. Using some of the components of public investment, such as health and education expenditure, we find a negative effect of resource rents, suggesting among other things that public spending of resource rents is directed more to other infrastructure investments.
Keywords: C23; E00; O10; 330; public investment; resource rents; growth; political institutions; sub-Saharan Africa